Molecular characteristics of immunocytes infiltration in primary central nervous system lymphoma - Zhang, Linyun; Sun, Fei; Lu, Xiaona; Wang, Xiaotong; Wang, Jie; Li, Jun; Xu, Yingsong; Kou, Daqing; Lv, Hongtao; Don, Bin (Frontiers in Genetics, 2022)
Background: Primary central nervous system lymphoma (PCNSL) is a rare B-cell lymphoma of central nervous system, which is often found in immunocompromised patients. The common clinical treatment of PCNSL is methotrexate(MTX) and whole brain radiation therapy. With the development of tumour immunology research, the tumour microenvironment of PCNSL is characterised by abnormal expression of different immune signature molecules and patients with PCNSL may benefit from tumour immunotherapy. Methods: In our research, RNA-seq data from 82 PCNSL patients were collated by mining the microarray data from the GEO database. All samples were classified into three types related to tumour immune response by the Cibersort algorithm and consistent clustering. Differential analysis of genes was used to uncover 2 sets of differential genes associated with tumour immunity. The ICI scores of each sample were obtained by PCA algorithm, and the relationship between ICI scores and immune checkpoint expression, immunotherapy and drug sensitivity was investigated. Genes associated with ICI scores and their functional characteristics were investigated by WGCNA analysis and PPI analysis, based on the ICI scores of each sample. Results: The tumour microenvironment in PCNSL has a greater relationship with the tumour immune response. ICI scores obtained from 375 differential genes were associated with multiple immune responses in PCNSL. PCNSL patients with higher ICI scores had a better tumour microenvironment and were sensitive to immunotherapy and some small molecule drug. This study also identified 64 genes associated with ICI scores, which may serve as important therapeutic and prognostic targets for PCNSL. Conclusion: The presence of multiple immunosuppressive responses in the tumour microenvironment of PCNSL which suggested that improving the immune function of PCNSL patients through immunotherapy and targeted therapies can be an effective treatment for PCNSL. And the ICI score and associated genes may also provide a better predictor of the clinical use of immunotherapy.